Access to Finance by Chilean Corporations - Sirtaine, Sophie (World Bank, Washington, DC, 2012)
The author assesses the extent to which Chilean firms have access to sufficient and adequate sources of funds. Access to finance has become an important issue for policymakers in Latin America. Small and medium enterprises (SMEs), in particular, complain that their lack of access to adequate sources of financing is an obstacle to their growth. Chile represents an interesting case study since it has one of the most developed financial markets in the continent, and thus great potential for using products suited to the needs and risk characteristics of SMEs. The author concludes that the largest firms have access to the whole range of financial instruments available in Chile. All smaller firms face financing constraints. She then analyzes the obstacles to downsizing access to the capital market and further increasing the penetration of banks in smaller segments.